Penerapan dan evaluasi algoritma bubble sort dalam pengurutan nilai mahasiswa dengan java dan representasi flowchart - Hasmi, Hasmi (Maliki Interdisciplinary Journal, 2025)
One of the advances in information and communication technology in Indonesia today is technology computer. A computer is a hardware device that works on several processes called an algorithm. Algorithms themselves are often found in everyday life, namely in sorting data, namely a method of comparing new elements with the old one and placed according to the smallest number to the largest. In this case, Sorting algorithm is the right choice because it has constant time and space efficiency. Regarding this algorithm, flowchart visualization and programming language are needed for in-depth understanding and implementation in real life.